B. C = (7 + 5)x
C. C = (7 + 5)(x + y)
D. C = 7y + 5x
Answer:
the correct answer is a. C = 7x + 5y
Answer:
The constant term in the function is 5
Step-by-step explanation:
we have
where
b is the y-intercept or the constant term of the function
Remember that
The x-intercept is the value of x when the value of the function is equal to zero
so
For x=-3 ----> f(x)=0
For x=-5 ----> f(x)=0
substitute any of the intercepts in the function
For x=-3
Verify with the other intercept
For x=-5
---> is true
therefore
The constant term in the function is 5
y= 2x-3
y=-2x+5
Answer:
Step-by-step explanation: